Maize Trade Policies in Zambia, Options for Growth : Policy Brief - World Bank (Washington, DC, 2022)
The Government of the Republic of Zambia aims to transform the economy to support economic growth and facilitate job creation. Central to the transformation agenda is a commitment to open trade regime for agricultural exports and imports. Zambia has a long history of import and export restrictions of agricultural commodities, maize in particular. This analytical work demonstrates that Zambia has lot to gain from committing to open agricultural trade. Partial equilibrium modelling estimates at US$97 million the annual gain of open borders for maize exports over the next decade, compared to a scenario of continued trade restrictions. Producer losses from maize trade restrictions between 2023 and 2030 are projected to amount to about US$1.42 billion. Such losses would cancel out the massive aid provided by the Government through the Farmer Input Support Program. While precise point estimates need to be interpreted with caution given the ongoing turmoil in global food markets, the direction and magnitude of these results cumulatively point to significant losses resulting from trade restrictions. The report details options for a comprehensive reform package to enable trade openness to effectively translate into additional income for farmers, traders, processors, and traders who participate in the sector.